Relation of the Myocardial Contraction Fraction, as Calculated from M-Mode Echocardiography, With Incident Heart Failure, Atherosclerotic Cardiovascular Disease and Mortality (Results from the Cardiovascular Health Study). - Maurer, Mathew S; Koh, William J H; Bartz, Traci M; Vullaganti, Sirish; Barasch, Eddy; Gardin, Julius M; Gottdiener, John S; Psaty, Bruce M; Kizer, Jorge R (Am J Cardiol, 2017)
We evaluated the association between 2-dimensional (2D) echocardiography (echo)-determined myocardial contraction fraction (MCF) and adverse cardiovascular outcomes including incident heart failure (HF), atherosclerotic cardiovascular disease (ASCVD), and mortality. The MCF, the ratio of left ventricular (LV) stroke volume (SV) to myocardial volume (MV), is a volumetric measure of myocardial shortening that can distinguish pathologic from physiological hypertrophy. Using 2D echo-guided M-mode data from the Cardiovascular Health Study, we calculated MCF in subjects with LV ejection fraction (EF) ≥55% and used Cox models to evaluate its association with incident HF, ASCVD, and all-cause mortality after adjusting for clinical and echo parameters. We assessed whether log2(SV) and log2(MV) were consistent with the expected 1:-1 ratio used in the definition of MCF. Among 2,147 participants (age 72 ± 5 years), average MCF was 59 ± 13%. After controlling for clinical and echo variables, each 10% absolute increment in MCF was associated with lower risk of HF (hazard ratio [HR] 0.88; 95% confidence interval [CI] 0.82, 0.94), ASCVD (HR 0.90; 95% CI 0.85, 0.95), and death (HR 0.93; 95% CI 0.89, 0.97). Moreover, the MCF was still significantly associated with ASCVD and mortality, but not HF, after adjustment for percent-predicted LV mass. Significant departure from the 1:-1 ratio was not observed for ASCVD or death, but did occur for HF, driven by a stronger association for MV than SV. In conclusion, among older adults without CVD or low LV ejection fraction, 2D echo-guided M-mode-derived MCF was independently associated with lower risk of adverse cardiovascular outcomes, but this ratiometric index may not capture the full relation that is apparent when its components are modeled separately in the case of HF.